How the climate resilient cities construction accelerates urban green transformation: impact effects and mechanism tests - Gao, Chen; Zhang, Cuiping; Wen, Ya; Wang, Chunhui (Frontiers in Environmental Science, 2025)
MethodsThis study constructs a quasi-natural experiment leveraging the pilot policy for climate resilient cities construction (CRCC), utilizing panel data from 296 prefecture-level cities in China spanning from 2006 to 2022. The Difference-in-Differences (DID) method is employed to identify the causal effect of CRCC on urban green transformation.ResultsEmpirical results show that CRCC significantly accelerates urban green transformation, with a 9.8% increase in green technology innovation. Mechanism analysis reveals that CRCC drives green transformation through industrial structure optimization and upgrading, as well as governmental incentive and regulatory actions. Additionally, the promoting effects of CRCC on industrial structure upgrading and governmental behavioral adjustments are weaker in resource-based cities, while in cities with higher administrative hierarchy, CRCC more effectively drives green transformation by accelerating industrial structure optimization and strengthening governmental incentive behaviors. Heterogeneity analysis shows that the positive effect of CRCC on green transformation is more pronounced in cities located on the southeast side of the Hu Line, and cities within the Yangtze River Economic Belt. Extended test results indicate that CRCC has a considerable enhancing effect on the green transformation of neighboring cities, and that green transformation exhibits a positive spatial spillover effect.ConclusionFor the first time, this study quantifies the causal effect of CRCC on urban green transformation using panel data, filling a research gap in the role of climate resilience policies in green development.